TEACHER EDUCATION: MODELS OF INITIAL TEACHER TRAINING - Pavié Nova, Alex (Revista Inclusiones, 2021)
Teacher education and pedagogy, in general terms, are a problem and/or an outstanding work -and also they are urgent tasks- ever since the different educational reforms started in the democratic Chile in 1990. At present, a new model of initial teacher training is being designed for this kind of teachers according to the complex adaptation process to the curricular approaches which are operating in the educational field. This study comprises the revision of the different approaches in the field of the initial teacher training. Moreover, some preliminary conclusions are included in the base of an analysis of the training politics and the verification of a training model.